Sistem Pendukung Keputusan Penentuan Karyawan Terbaik Berdasarkan Kinerja Menggunakan Metode TOPSIS - Miya Putri Daulay; Risa Ermis Claudia Malau; Nelly Astuti Hasibuan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The best employee is someone who really has a big influence on the development and progress of the company, because a company really needs employees who have high loyalty and the ability to improve the progress of a company or forum. A company or forum cannot run well if there is no employee, because the progress of a company depends on these human resources. However, when determining the best employees, fraud often occurs because the determination of the best employees is still done manually which will later lead to a subjective element so that in determining the best employees based on performance there are 4 criteria including Discipline, Cooperation, Work Period, and Skills. So with this it is very necessary to have a decision support system in solving problems with the TOPSIS method which will later produce preference values ​​from alternatives and predetermined criteria. The final result is obtained by using the TOPSIS method where the highest alternative is A5 by obtaining a value of 0.9659 on behalf of Reza Yunanda Lubis. The method is also a very simple method and is also highly recognized as a very precise and accurate decision-making alternative